Using Humour for Generating and Maintaining Interest in Mathematics among Secondary School Students in South Sudan Re-settled Communities. Issue 2 (4th May 2019) - Tap, William D.; Mtetwa, David K.; Vere, Joseph C.
Abstract : This paper reports on some aspects of an investigation on the impact of an instructional approach aimed at generating and maintaining students' interest in mathematics for secondary school students in displaced and re-settled communities in South Sudan. Two groups of Grade 11 students, an experimental group (E-group) and a control group (C-group), participated in the study. The E-group ( n  = 31) was taught using a Humour-supported Instructional Approach (H-SIA) and the C-group ( n  = 20) was taught using a Regular Instructional Approach. Preliminary indications from the pilot phase of the main study suggest that the method of instruction (H-SIA) generates and maintains at least similar levels of interest as the regular Regular Instructional Approach. The H-SIA also suggests some slight modifications and enhancement to the Interpersonal Competent Communication Model, the recommended existing guiding theory for humour communication in the classroom. It is concluded that H-SIA does indeed generate and maintain interest in mathematics in the classroom. Hence, it is recommended that mathematics teachers should consider infusing humour into their lessons to enhance students' interest in mathematics.